Light chain of a public SARS-CoV-2 class-3 antibody modulates neutralization against Omicron - Patel, Anamika; Kumar, Sanjeev; Lai, Lilin; Keen, Meredith; Valanparambil, Rajesh; Chakravarthy, Chennareddy; Laughlin, Zane; Frank, Filipp; Cheedarla, Narayanaiah; Verkerke, Hans P.; Neish, Andrew S.; Roback, John D.; et al. (Cell reports (Cambridge), 2023)
The pairing of antibody genes IGHV2-5/IGLV2-14 is established as a public immune response that potently cross-neutralizes SARS-CoV-2 variants, including Omicron, by targeting class-3/RBD-5 epitopes in the receptor binding domain (RBD). LY-CoV1404 (bebtelovimab) exemplifies this, displaying exceptional potency against Omicron sub-variants up to BA.5. Here, we report a human antibody, 002-S21B10, encoded by the public clonotype IGHV2-5/IGLV2-14. While 002-S21B10 neutralized key SARS-CoV-2 variants, it did not neutralize Omicron, despite sharing >92% sequence similarity with LY-CoV1404. The structure of 002-S21B10 in complex with spike trimer plus structural and sequence comparisons with LY-CoV1404 and other IGHV2-5/IGLV2-14 antibodies revealed significant variations in light-chain orientation, paratope residues, and epitope-paratope interactions that enable some antibodies to neutralize Omicron but not others. Confirming this, replacing the light chain of 002-S21B10 with the light chain of LY-CoV1404 restored 002-S21B10’s binding to Omicron. Understanding such Omicron evasion from public response is vital for guiding therapeutics and vaccine design. [Display omitted] •Characterizes a class-3 mAb encoded by the rare public clonotype IGHV2-5/IGLV2-14•mAbs of this public clonotype heterogeneously neutralize the SARS-CoV-2 variants•Structure reveals that light chain in CDR1 and CDR3 mediates Omicron neutralization Based on structural and sequence comparisons, Patel et al. describe how the molecular features of the light chain of a public antibody modulate its broadly neutralizing properties against SARS-CoV-2 variants, specifically targeting the Omicron variant.